Body image, physical activity, and sport: A scoping review - Sabiston, C.; Pila, E.; Vani, M.; Thogersen-Ntoumani, Cecilie (Elsevier BV, 2018)
© 2018 Objectives: This scoping review explored the associations between physical activity, sport, and body image. Design: Scoping review. Method: The studies were identified and selected using broad search criteria using MEDLINE, EMBASE, and PsycINFO via Ovid and CINAHL, Gender Studies and Sport Discus via EBSCO, from January 1, 2008 up to May 15, 2018 for English peer-reviewed publications. A rigorous evaluation following specific exclusion criteria ensued and 210 publications (182 quantitative, 26 qualitative, and 2 mixed-methods studies) were indexed and summarized using frequency counts. Results: The studies were focused exclusively on sport (14.8%) or physical activity (defined as structured or leisure; 85.2%). The majority of the quantitative studies (58.2%) focused on the relationship between physical activity or sport and body image whereas 41.8% explored how body image was either a protective factor or deterrent for physical activity or sport participation. Four qualitative studies specifically examined the intersection of physical activity or sport and body image experiences. Based on the frequency of reported findings in the journal articles, participation in physical activity and sport was related to less negative and more positive body image. Negative body image was linked to lower physical activity and sport participation and was discussed qualitatively as a barrier to participation. Positive body image was associated with greater participation in physical activity and sport. There was no empirical focus on the bi-directional and reciprocal associations between physical activity or sport and body image, thus precluding any causal conclusions. Conclusions: Future research is needed using integrative conceptual frameworks and research designs that emphasize and delineate the causal, bi-directional, and reciprocal associations between body image and physical activity and sport behaviors.